Effect of Re addition on the microstructure and mechanical properties of AlCoCrFeNi2.1 eutectic high-entropy alloy. (March 2023) - Zhang, Xiaobo; Li, Bo; Zeng, Long; Yi, Jiaojiao; Wang, Binqiang; Hu, Conghui; Xia, Mingxu
Abstract: Alloying is an important and effectivise means to realize mechanical properties improvement of alloys and HEAs. In this article, series of (AlCoCrFeNi2.1 )100-x Rex high entropy alloys, where x = 0, 0.3, 0.6 and 1 (wt.%), were prepared using a centrifugal casting method, and the effect of Re content on the phase composition, microstructure and mechanical properties was investigated. With Re addition increase, the NiAl-enriched phases in the base alloy decreased or even disappeared, and the lamellar spacing of eutectic phases decreased. Moreover, FeCoCr-enriched primary dendrite phases emerged in the alloy system after Re addition and its volume increased dramaticly when Re addition increased to 1 wt%. The reason for this phenomenon is that the addition of trace Re element makes the shift of eutectic composition point to hypereutectic composition point. Additionally, both yield stress and ultimate tensile stress were increased with Re addition, but the elongation decreased. Highlights: Re was added into AlCoCrFeNi2.1 eutectic high entropy alloy to improve the mechanical properties. The size and quantity of NiAl-rich phases decreased after Re addition. Re element tends to be enriched in CoCrFe enriched phase. Addition Re enhanced the tensile stress, whereas the elongation decreased.